Awareness and Knowledge Levels of Adults related to Pest Control in Malatya City Center [Malatya Kent Merkezinde Yetiskinlerin Hasere Mucadelesine Iliskin Farkindaliklari ve Bilgi Duzeyleri] - Erkan Pehlivan; Ali Ozer; Guray Ozen; Elvan Turkol; Gulsen Gunes; Rukuye Aylaz (Medicine Science, 2013)
This study was carried out to evaluate knowledge level and awareness of adults related to pest control in Malatya city center. This cross-sectional study was conducted between March and October alternately the struggle against larval and adult vectors was done every two weeks in the suburbs of city. The districts where to struggle against larvae constituted of this research universe. In health station -based 30 cluster sampling created, the 20-item questionnaire was applied randomly in 420 household with help of team chief of spraying under the supervision of researchers. 381 adult subjects answered the questionnaire. The study participation rate was 90.7%. In evaluation and analysis of research data the independent samples Student\'s t-test, Chi-square and ANOVA were used. The 44.9% were male and 55.1% female of 381 participants. Mean age was 38.4 ± 12.7, and 10.5% illiterate, 34.9% literate or primary school graduates, 46,4% were secondary or high school and 8.1% were in the higher education of the participants. 92.6% of the participants awareness about the mosquitoes, 76.9% the houseflies, 29.1% the midge, and also 36.5% of subcejts were announced that were made struggle against ticks with drugs. Approximately 1/3 of participants stated that the chemical agents used for pest control were harmful to human health (32.8%) and the environmental health (35.2%) also. The men who answered to the total 13 questions correctly average 6.1 ± 1.9, and for women average 6.2 ± 1.9 was similar to each other (p = 0.885). Average scores of the participants of those under the age of 30 was 6.4 ± 2.1, the ages between 40-49 was 6.1 ± 1.9 and the ages over 60 was 5.6 ± 1.7. There was no statistically significant difference with average knowledge scores although it decreased with age (p = 0.218). The mean scores of illiterates information was 5.8 ± 2.0, and with 7.3 ± 2.0 in the higher educated ones was difference statisticially (p=0.001). Although the people largely informed on the struggle against pests in the city center, the lower knowledge scores was held. It can be said that the people do not have enough awareness about the dangers of chemical agents to human and environmental health. As a result, to raise public awareness about the integrated pest management is needed. [Med-Science 2013; 2(4.000): 907-20]